Uniqueness of the solution of the Cauchy problem for the partial differential equations and the convolution equations - Piętka, Marek (Annales Mathematicae Silesianae, 1991)
The method of construction of classes of uniqueness of solutions for differential and convolutional equations (containing the classical partial difierential equations) is presented in this paper. It tries to explain the anomaly of uniqueness of solutions for the Laplace and wave equations and non-uniqueness for the equation of heat.